Six Sigma method to assess the quality of the service in a gas utility company (2022)
A method to evaluate the quality of service of a customer service centre is proposed based on Six Sigma, and through an empirical and rational approach that allowed an objective perspective during the development of the study. The quality dimensions that structure the service were identified to consolidate their valuation and to analyse the results in terms of defects per parts per million, sigma level and yield. As a result, it was found that the performance of the service quality dimensions was satisfactory due to the results obtained by all the calculated metrics, obtained an average yield percentage above 97% in the two periods, and all dimensions of quality were above the critical sigma value with a level above 3.43 which shows that the centre provided a satisfactory service process during these periods. Finally, the proposed method associated with the contextualisation of the quality dimensions of the service is significantly innovative and important for the scientific and business community.